EP650 Ultrasound screening for endometrial abnormalities in patients on tamoxifen. (1st November 2019) - Vranes, B; Vulic, N; Mitrovic, P; Stojanovic, V; Filipovic, N; Kusljevic, N; Tomovic, D; Matavulj, N; Cegar, O
Abstract : Introduction/Background: The accuracy of the ultrasound screening for endometrial abnormalities in absence of bleeding is a subject of debate. We compared pathology reports in 92 postmenopausal patients who underwent D&C based on the ultrasonographic finding of endometrial hyperplasia in the absence of bleeding. The literature review presents data low with low ultrasound accuracy for endometrial abnormalities, at a range of 1:100 or less for asymptomatic patients. Methodology: Retrospective case-control study was conducted in 2013–2014 and 92 patients were selected. All patients underwent D&C due to endometrial hyperplasia diagnosed with ultrasound only. Sixty patients were postmenopausal on Tamoxifen treatment for breast cancer and 32 patients were from general population. There was no bleeding registered in any of the patients prior to D&C. The threshold for endometrial thickness was 6 mm for asymptomatic patients from general population, and 4 mm for Tamoxifen receiving patients. No patients were evaluated for endometrial abnormalities before onset of tamoxifen treatment. Results: Mean endometrial thickness was 15.7 mm in general population and 7.8 mm in Tamoxifen group. In general population group endometrial cancer was detected in 1 patient (3.1%). In 9 patients (28%) histology revealed simple endometrial hyperplasia, in 7 (22%) endometrial polyp while 14 (44%) had normal endometrium or atrophy. One of 60 Tamoxifen patients (1.67%) was found with adenocarcinoma. 1 (1.67%) was found with cystic hyperplasia, 6 (10%) were found with cystic polyps, and 1 (1, 67%) with simple polyp. Seventy three percent of patients were found with no endometrial abnormalities. Conclusion: The accuracy of ultrasound in screening for endometrial abnormalities is low, and it is hard to justify the rate of invasive diagnostic procedures as D&C. We recommend adopting guidelines as ACOG 336 in identifying high risk patients. Evident uterine bleeding should be invasively investigated. Disclosure: Nothing to disclose.